Molecular Study of Benzimidazole Resistance in Teladorsagia circumcincta Isolated from Sheep in North of Iran - Rahim NEMATI; Aliasghar BAHARI; Pezhman MAHMOODI; Alireza SAZMAND (Iranian Journal of Parasitology, 2019)
Background: Resistance to benzimidazole (BZ) compounds is common in Teladorsagia circumcincta populations in sheep and goats worldwide. Given the importance of anthelmintic resistance and shortage of information on single nucleotide polymorphisms (SNPs) in this prevalent nematode in Iran, this study was conducted.